Optimalisasi Tugas dan Fungsi Camat dalam Pelayanan Publik Kecamatan Siritaun Wida Timur Kabupaten Seram Bagian Timur - Rumain, Sahidin; Tuanaya, Wahab; Kotaromalos, Amir Faisal (Journal of Government Science Studies, 2023)
The purpose of this study is to describe the optimization of the duties and functions of the sub-district head in public services in District of Siritaun Widatimur. This study uses qualitative research methods through observation, interviews and documentation. The data was obtained at the Siritaun Widatimur sub-district office through the sub-district head, sub-district secretary, officials, five community leaders and five youth leaders. This study aims to determine the duties and functions of the sub-district head in providing services to the community in the Siritaun Widatimur sub-district. The results of this study indicate that the functions and duties of the sub-district head in providing public services are considered good, although there are some individuals or individuals who are not professional in doing their work.